2020
DOI: 10.2147/cmar.s230466
|View full text |Cite
|
Sign up to set email alerts
|

<p>Melatonin Regulates Cisplatin Resistance and Glucose Metabolism Through Hippo Signaling in Hepatocellular Carcinoma Cells</p>

Abstract: Introduction and Aim: Hepatocellular carcinoma (HCC) is a primary malignancy that occurs in the liver. Clinical cases have been recorded worldwide, particularly in the Saharan area and Asia. In the present work, we aimed to probe the characteristics of melatonin involved in human HCC development, especially in cisplatin resistance and glucose metabolism. Methods: Two HCC cells, HepG2 and Hep3B cells, were treated with melatonin. Cell cycle test was then used to define the role of melatonin in cell progression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 60 publications
(55 reference statements)
2
15
0
Order By: Relevance
“…Herein, the assessment of the OXPHOS/glycolysis equilibrium showed on one hand reduction of oxidative phosphorylation with increased proton leak accompanied by enhanced oxidative stress while glycolytic capacity or glucose uptake were distinctly arrested on the other hand. These changes are in line with latest reports of Mi & Kuang 86 or Puente‐Moncada et al 87 where glucose uptake significantly decreased by melatonin in HepG2 hepatocarcinoma or in tumour xenograft mouse model, respectively. Considering earlier reports, melatonin has been described as an effective anti‐apoptotic, anti‐inflammatory and anti‐oxidative molecule in human keratinocytes or melanocytes under stress conditions 8,9,11‐13,31 .…”
Section: Discussionsupporting
confidence: 92%
“…Herein, the assessment of the OXPHOS/glycolysis equilibrium showed on one hand reduction of oxidative phosphorylation with increased proton leak accompanied by enhanced oxidative stress while glycolytic capacity or glucose uptake were distinctly arrested on the other hand. These changes are in line with latest reports of Mi & Kuang 86 or Puente‐Moncada et al 87 where glucose uptake significantly decreased by melatonin in HepG2 hepatocarcinoma or in tumour xenograft mouse model, respectively. Considering earlier reports, melatonin has been described as an effective anti‐apoptotic, anti‐inflammatory and anti‐oxidative molecule in human keratinocytes or melanocytes under stress conditions 8,9,11‐13,31 .…”
Section: Discussionsupporting
confidence: 92%
“…In a more extensive study, our group demonstrated that in vitro administration of melatonin (0.1–10 mM for 10 days) causes a dose- and time-dependent reduction of HepG2 human HCC cell viability; these results were associated with modifications in the cell cycle kinetics, with an increase in the percentage of cells in the G0/G1 phase accompanied by a reduction in cell counts in G2/M phase; these changes were related to the induction of p53 expression and subsequent activation of p21 (a potent inhibitor of cell cycle kinases—CDKs) [ 10 ]. Results were recently confirmed by other authors, not only in HepG2 but also in Hep3B HCC cells; they reported a reduction of cyclin D1 expression and the induction of cell cycle arrest by 1 and 2 mM melatonin [ 59 ].…”
Section: Resultssupporting
confidence: 72%
“…In vitro experiments using Bel-7402, SNU-449, HepG2 and Hep3B HCC cells have demonstrated that combined treatment of cisplatin with 1 mM melatonin increases the intrinsic pathway of apoptosis and inhibits the NF-κB/COX-2 pathways, improving the therapeutic efficiency of cisplatin in HCC [ 43 ]. More recently, it has been also shown that, in HepG2 and Hep3B HCC cells, 1 and 2 mM melatonin heightens cisplatin-induced apoptosis by downregulating different antiapoptotic proteins (including Bcl-2, Bcl-xL or Mcl-1), and upregulating cleaved caspase-3 and PARP, effects apparently related to activation of Hippo signaling pathway, which promotes apoptosis and suppress cell proliferation [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lower mRNA and protein levels of YAP were further identified as consequences of melatonin intervention. On the other hand, higher levels of YAP were detected in HepG2 and Hep3B cells without melatonin treatment; these partially reversed the melatonin-supported suppression of proliferation, metabolic reprogramming and apoptosis mediated by cisplatin [ 108 ]. Furthermore, recent evidence showed the regulatory effects of melatonin on nickel-induced metabolic changes.…”
Section: Structural and Functional Aspects Of Melatoninmentioning
confidence: 99%